PEMODELAN HUBUNGAN KOINTEGRASI HARGA CPO DAN KINERJA INDEKS SAHAM SYARIAH INDONESIA MENGGUNAKAN VECM - Dewi Santri; Alwahidin Alwahidin (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Forecasting stock movements will usually be more accurate if the model considers the involvement of other variables that may have an effect. This study models the long-term dynamic relationship between the Indonesian Sharia Stock Index (IDX Syariah) performance and changes in Crude Palm Oil (CPO) prices. IDX Syariah and CPO data are known to be non-stationary and are modelled using Vector Error Correction Model (VECM) analysis. The cointegration test results of the two variables show a significant long-term relationship between the IDX Syariah and CPO variables. The Impulse Response Function (IRF) graph shows that the performance of IDX Syariah will respond to the movement of the new CPO value from the third lag period to the sixth lag period. IDX Syariah negatively responded to CPO in the third lag and fluctuated up until the sixth period. This finding means that CPO prices negatively respond to changes in the Indonesian Sharia Stock Index after three to six periods, and new prices are formed in the CPO commodity market.